Reverse Koebnerization in a linear oral lichenoid lesion: A case report - Prashanth Panta; Archana Andhavarapu; Sachin C. Sarode; Gargi Sarode; Shankargouda Patil (Clinics and Practice, 2019)
The spectacle of Koebner’s phenomenon (KP) is interesting in that trauma precipitates a subset of pathologically distinct conditions, indicating the subtle interplay between sensitization and dermato-mucosal integrity. KP is interesting because, if factors initiating it are controlled, then it may be possible to prevent these debilitating conditions through induction of reverse Koebnerization. Herein, we present a report of a patient with an erosive lesion, localized to the occlusal plane on buccal and lingual mucosa, that interestingly subsided following 1 week after a dental scaling procedure. This report analytically describes the role of dental calculus and cuspal trauma as important triggers surrounding the genesis of oral lichenoid lesion and oral lichen planus. An engaging discussion on these closely related enigmatic entities forms the central theme of this report.